La punta del iceberg - Cánovas, David (Barcelona Cameo media, 2016)
A large multinational company is shaken by the suicide of three employees. The company sends a director, Sofia Cuevas, to conduct an internal investigation. She discovers an unhealthy work environment: a pathogenic form of management where the individual is relegated to a minor role and the only priority is the bottom line. But, what are the real reasons that lead a man to suicide?
Maribel Verdú, Carmelo Gómez, Fernando Cayo, alex García, Ginés García Millán
No recomendada para menores de 16 años
Idiomas : Inglés y castellano
Keywords: Películas cinematográficas -- DVD